1990
DOI: 10.1038/clpt.1990.210
|View full text |Cite
|
Sign up to set email alerts
|

Combined α/β-blockade versus β1-selective blockade in essential hypertension in black and white patients

Abstract: The purpose of this multicenter investigation was to determine the efficacy and safety of the alpha/beta-blocker labetalol versus the beta 1-selective beta-blocker atenolol in white and black patients with essential hypertension. Equal numbers of black and white patients were enlisted to form four treatment groups (white patients taking either labetalol or atenolol and black patients taking either labetalol or atenolol). Two hundred ninety-two patients (152 white and 140 black patients) with essential hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Indeed, this study found that there was, in fact, a small increase in the supine SBP among black hypertensives following labetalol therapy, that higher doses of labetalol were required among black populations to achieve BP control, and that atenolol was markedly more effectively than labetalol in lowering supine BPs among black patients. 29 We also note a smaller study from Jennings and Parsons 30 which also shows that labetalol was more effective in white populations.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, this study found that there was, in fact, a small increase in the supine SBP among black hypertensives following labetalol therapy, that higher doses of labetalol were required among black populations to achieve BP control, and that atenolol was markedly more effectively than labetalol in lowering supine BPs among black patients. 29 We also note a smaller study from Jennings and Parsons 30 which also shows that labetalol was more effective in white populations.…”
Section: Discussionmentioning
confidence: 73%
“…2,14,15 Studies have suggested that African-Americans with hypertension are more responsive to diuretics and calcium channel blockers than other antihypertensive agents. 13,16,17 This study had inadequate power to detect a significant difference in compliance, health perception, and patient satisfaction. Although no difference in these factors was found, compliance may have been greater in the intervention group.…”
Section: Discussionmentioning
confidence: 95%
“…In these subjects, NSAIDS should be discontinued, spironolactone should be started at 12.5 mg daily and serum potassium and creatinine should be closely monitored; subjects should also be educated to avoid food or supplements rich in potassium. In case the BP is still above target, we prefer combined α-β blockers such as labetalol or carvedilol to pure β-blockers due to their suggested better BP control [38]. If β blockers are contraindicated, peripheral α-blockers may be considered: a recent retrospective study showed that doxazosin at a mean dose of 4 mg/day further decreased SBP by 16 mmHg and DBP by 7 mmHg in subjects with RH [39].…”
Section: Treatment Of Rhmentioning
confidence: 99%